Situation Report: Bulgaria, 12 August 1971 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Private Artisans Again to Help Solve Supply Problems Tano Tsolov Predicts Difficulties in Comecon Integration Bulgarian Warships Join Soviet Vessels in Mediterranean On the Literary Front - Criticism and Prescriptions